Effect of Using Mental Training Method on Precision of Passing Skills from for Head pass and over hand Serve in Volleyball. - Fattah, Nabaz A. (Humanities Journal of University of Zakho, 2019)
The aim of the study is to reveal the effect of using mental training method on the precision of performing some main skills in volleyball. The sample of the study consists of 30 second year students of the School of Sports Education at Koya University. The researcher used an experimental program due to its suitability to the nature of the study. The sample was divided into two equal groups of 15 students. Equivalence procedure was conducted for both groups for the variables of ( age, height, mass, intelligence, manifestation of attention) , sport mental perception and some elements of effective physical and movement fitness that influence the precision of performing passing skills from for head pass and over hand serve. The researcher used questionnaires, tests and measurements as means for data collection. Then, two educational programs were constructed. The first program was for the second year students. The second program was the same as the first one but mental training method was added to it. Each program consisted of 6 teaching units and conducted for a duration of 6 weeks and each unit lasted for 90 minutes. The researcher used the following statistical procedures: arithmetic mean, standard deviation, T-test of related means and T-test of unrelated means as a means to deal with the data. The researcher arrived at the conclusion that the experimental group whom the educational program (mental training included) was conducted on was more successful than the control group in the post-tests whom carried out a program on performing passing skills from for head pass and over hand serve in volleyball.